Conjunto de características para teste de desempenho : uma visão a partir de ferramentas - Costa, Leandro Teodoro (2012)
Currently, the development of systems in the software industry has increased. As far as the need of customers in automate their processes grows, their demand to improve the quality of computational systems also increases. In this sense, software testing has a fundamental role. Despite of the benefits provided by testing, most of it is performed manually and without a theoretical basis, making the testing activity slow and inefficacious. An alternative for solving this problem is the use of test automation tools. In addition to accelerate the work of testers, these tools provide a higher quality and efficiency for the testing process. However, even though these tools can make the testing process faster, the test case generation for them is performed manually. The ideal is to also automate the generation and execution of test cases for these tools. In order to overcome this limitation, this work proposes a set of features which includes the information necessary for the generation and execution of real test cases for performance testing tools. Based on information from this set, we developed plugins for a product line of tools for model-based testing called PLeTs (Product Line Testing Tools). These plugins implement the automatic generation and execution of test scripts and test scenarios using two performance testing tools, HP LoadRunner e Microsoft Visual Studio. In order to show the feasibility of the proposal of this work, we performed a case study, which is based on the automated generation and execution of test cases using products generated by the product line PLETs.